Exploring Business Analytics Initiatives in the Accounting Literature: are all accounting areas equal? - Araujo, Leticia Silva; Behr, Ariel; Marcolin, Carla; Scornavacca, Eusebio (Advances in Scientific and Applied Accounting, 2024)
Objectives: The goal of our research is to understand why Business Analytics (BA) practices are selected and how they are adopted across various accounting areas. To achieve this, our study maps and analyzes the analytics initiatives documented in the literature that have been adopted by the accounting profession, categorizing these initiatives by accounting area. Method: We conducted a Systematic Literature Review, drawing on publications from the Web of Science and Scopus databases, as well as prominent journals in Information Systems and Accounting Information Systems. Data analysis utilized categorical content analysis with theory- and data-driven codes, aligned with research objectives. Results: Our results provide a comprehensive mapping of Business Analytics literature in accounting, detailing the dimensions - Domain, Orientation, and Technique - by accounting area. This mapping provides a deeper understanding of the relationship between the specific characteristics of each accounting area and the use of Business Analytics. Additionally, we propose a taxonomy based on usage purposes in each area. Finally, we present a research agenda, summarizing key contributions and offering suggestions for future research. Contributons: This research contributes academically by enabling a comparison of Business Analytics adoption and use across different accounting areas, highlighting those with greater maturity in Business Analytics. Additionally, the proposed taxonomy, which considers the purpose of BA within these accounting areas, helps clarify and promote alignment between the accounting discipline and analytics techniques, reducing both conceptual and practical confusion. Furthermore, this research serves as a foundation for accounting professionals to develop their skills in analytics initiatives.